The Divide between Applied Research and Operations in Health Information Technology Advancement: Reducing the Gap. (September 2015) - Saleem, Jason J.; Militello, Laura G.; Russ, Alissa L.; Wilck, Nancy R.
This practice-oriented presentation describes several factors that contribute to the divide between applied research and operations for health information technology (HIT). Factors and corresponding recommendations were drawn from experiences working in both research and operations positions as human factors professionals within a large healthcare system, the Veterans Health Administration (VHA). We offer specific recommendations for addressing each of these factors to help reduce the gap. Although our findings and recommendations were derived from our VHA experience, we expect many of the lessons learned are relevant to other major healthcare organizations. Indeed, we strongly suspect that the factors presented represent fundamental differentiators between researchers and operational-based professionals. Understanding these differences and findings ways to bridge them is essential for advancing HIT.